Biocomposite Coatings Delay Senescence in Stored Diospyros kaki Fruits by Regulating Antioxidant Defence Mechanism and Delaying Cell Wall Degradation - Muhammad Shahzad Saleem; Shaghef Ejaz; Walid F. A. Mosa; Sajid Ali; Hasan Sardar; Muhammad Moaaz Ali; Sami Ullah; Hayssam M. Ali; Anna Lisek; Muhammad Akbar Anjum (Horticulturae, 2023)
Climacteric rise in the rate of respiration and ethylene production in harvested persimmon (Diospyros kaki) fruits leads to early onset of fruit tissue senescence. Therefore, this study was carried out to maintain the quality of stored persimmons by using edible coatings. For this purpose, Aloe vera gel was combined with food hydrocolloids, gum arabic or tragacanth gum, and applied on persimmon fruits that were stored for 20 days at 20 ± 1 °C and 80–85% RH. Biocomposite coatings, compared to control, remarkably reduced weight loss, decay incidence, respiration rate, ethylene production, electrolyte leakage, malondialdehyde, H2O2 and superoxide anion content in stored fruits. The use of composite coatings inhibited colour change by reducing the accumulation of total carotenoids, maintained higher antioxidative enzymes activity and suppressed the activity of cell wall degrading enzymes, resultantly preserving cell wall components. Composite coated fruits exhibited the least change in biochemical attributes and higher sensory scores in comparison with non-coated fruits at the end of the storage period. In conclusion, Aloe vera gel/gum arabic was the most effective coating treatment before storing persimmons.